1997
DOI: 10.1063/1.119138
|View full text |Cite
|
Sign up to set email alerts
|

High-carrier-density electron dynamics in low-temperature-grown GaAs

Abstract: Articles you may be interested inTransient reflectivity as a probe of ultrafast carrier dynamics in semiconductors: A revised model for lowtemperature grown GaAs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 8 publications
0
36
0
Order By: Relevance
“…The initial fast exponential decay ( ~100 -300 fs), is caused by the thermalization of the carriers due to electron-phonon interactions and the time scale observed here is typical for III-V semiconductors 24,25,26 . This part of the signal may also have some significant contribution from the GaAs buffer layer and the substrate for λ 870 nm.…”
Section: A the Three Processesmentioning
confidence: 99%
“…The initial fast exponential decay ( ~100 -300 fs), is caused by the thermalization of the carriers due to electron-phonon interactions and the time scale observed here is typical for III-V semiconductors 24,25,26 . This part of the signal may also have some significant contribution from the GaAs buffer layer and the substrate for λ 870 nm.…”
Section: A the Three Processesmentioning
confidence: 99%
“…17 Relaxation processes of photoexcited carriers in LTGaAs have been studied by means of the pump-probe method. [18][19][20][21][22][23][24][25] According to these studies, photoexcited carriers are first trapped by excess As point defects in subpicoseconds and recombine in relatively long times in as-grown LT-GaAs. It is suggested that photoexcited electrons are trapped by positively ionized As Ga and holes are trapped by negatively ionized V Ga .…”
Section: Introductionmentioning
confidence: 98%
“…It can be seen that the relaxation time of fast decay and slow one is increased with pump fluence. This trend is expected for surface states filling [11], which may inhibit carrier lifetime. …”
Section: Resultsmentioning
confidence: 99%